Roles of the northern goddess - Davidson, H. R. Ellis (Hilda Roderick Ellis), 1914-2006 (Routledge, 1998)
By investigating women's special skills related to goddess cults together with legends and popular traditions, the author explores the importance of the goddess as a subject for study today.